2021
DOI: 10.1038/s41598-021-93907-0
|View full text |Cite
|
Sign up to set email alerts
|

Association between comorbid asthma and prognosis of critically ill patients with severe sepsis: a cohort study

Abstract: Basic research suggests some contributing mechanisms underlying asthma might at the same time benefit patients with asthma against sepsis, while the potential protective effect of comorbid asthma on prognosis of sepsis has not been well studied in clinical research. The study aimed to assess the association between comorbid asthma and prognosis in a cohort of patients admitted to intensive care unit (ICU) with severe sepsis. Patients with severe sepsis admitted to ICUs were included from the MIMIC-III Critical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…While almost all comorbidities under investigation were of similar importance with regard to 60-day mortality in COVID-19 and Sepsis as well as in COVID-19 and ARDS, we found a differential effect for asthma. Asthma showed a stronger association to 60-day mortality in COVID-19 than in Sepsis possibly relating to previous evidence that asthma is associated to a better prognosis in Sepsis 28 . This finding is also consistent with a previous study in which an independent association was found between asthma and COVID-19 ICU-mortality 15 .…”
Section: Discussionsupporting
confidence: 51%
“…While almost all comorbidities under investigation were of similar importance with regard to 60-day mortality in COVID-19 and Sepsis as well as in COVID-19 and ARDS, we found a differential effect for asthma. Asthma showed a stronger association to 60-day mortality in COVID-19 than in Sepsis possibly relating to previous evidence that asthma is associated to a better prognosis in Sepsis 28 . This finding is also consistent with a previous study in which an independent association was found between asthma and COVID-19 ICU-mortality 15 .…”
Section: Discussionsupporting
confidence: 51%
“…[15][16][17][18] Balthazar CT grading is a grading method to evaluate the lesions of pancreatic parenchyma and surrounding tissues according to pancreatic morphology, inflammation and other conditions. [19,20] Studies have shown that the larger the volume of necrosis in the pancreas and peripancreatic area, the higher the density of necrosis, the slower the absorption and dissipation, the more serious the erosion effect on peripancreatic tissue, and the larger the CT attenuation value. [21,22] Multivariate logistics analysis of this study showed that Balthazar CT grade, necrotic volume and mean attenuation value were independent risk factors for poor prognosis in patients with acute necrotizing pancreatitis.…”
Section: Discussionmentioning
confidence: 99%
“…40 Activated immune cells may have protective effects against infections. 5,41 Furthermore, scholarly evidence suggests that unique immunoregulatory pathways may be involved in mitigating the systemic spread of inflammatory reactions in individuals with asthma, potentially reducing the severity of sepsis. 42,43 The prevalence of Th2-type immune responses may also aid in dampening the hyperinflammatory reactions associated with sepsis.…”
Section: Discussionmentioning
confidence: 99%